GENDER JUSTICE AND WOMEN EMPOWERMENT: Legal Measures in India - Dev , Shampa; Kamath, Vasundhara (Journal of Dharma, 2016)
Educating the girl child, creating job opportunities, putting women in decision making roles, and making pro-women laws protecting them from oppression were some of the many steps that were designed for women's empowerment. But many years down the line the quest for a just society that values women and accords them the necessary dignity and respect is still on. A paternalistic approach with the assumption that women were victims of the social divide was adopted to rid women of their troubles. Being vulnerable they required protection; and so a number of measures were required and adopted to empower her. The authors argue that the flaw in the law is in its paternalistic approach, which does not accord autonomy of self-governance or self-direction. The autonomy needs to be redefined as a relative idea where a just and compassionate society nurtures its members and creates social conditions that strengthens autonomous decisions, instead of impeding them, for the realization of their full potential. It can neither be a masculine versus feminine argument nor be attained in isolation.